Florivory and Pollination Intersection: Changes in Floral Trait Expression Do Not Discourage Hummingbird Pollination - Tunes, Priscila; Dötterl, Stefan; Guimarães, Elza (Frontiers in Plant Science, 2022)
Many flowers are fed on by florivores, but we know little about if and how feeding on flowers affects their visual and chemical advertisement and nectar resource, which could disrupt pollination. Here, we investigated if damages caused by florivores compromise a Neotropical hummingbird pollination system, by modifying the floral advertisements and the nectar resource. We surveyed natural florivory levels and patterns, examined short-term local effects of floral damages caused by the most common florivore, a caterpillar, on floral outline, intra-floral colour pattern and floral scent, as well as on the amount of nectar. Following, we experimentally tested if the most severe florivory pattern affected hummingbird pollination. The feeding activity of the most common florivore did not alter the intra-floral colour pattern, floral scent, and nectar volume, but changed the corolla outline. However, this change did not affect hummingbird pollination. Despite visual floral cues being important for foraging in hummingbirds, our results emphasise that changes in the corolla outline had a neutral effect on pollination, allowing the maintenance of florivore–plant–pollinator systems without detriment to any partner.